Filosofíe en universitêre wetenskapsbeleid: caritas, sapientia, scientia - Venter, J. J. (Koers, 1997)
What could a philosopher contribute to scholarship in terms of policy? It is possible to present a philosophical diagnosis of Modern Western culture, which determines scholarship internationally. Through this diagnostic analysis, an attempt is made to unmask the Hobbesian principles - in Girardian terms: "mimetic desire " - behind the economistic technocratic tendency of culture, and the transformation of scholarship into subjective power which imposes its structure onto "reality". It is argued that the university should row against this current, attempting to stabilize knowledge production, and to open up avenues to creative relational knowing and wisdom by adopting the caritas-principle as the basis of scholarship. Some practical consequences are drawn from this point of departure.